Adiposity is associated with blunted cardiovascular, neuroendocrine and cognitive responses to acute mental stress. - Alexander Jones; Merlin R McMillan; Russell W Jones; Grzegorz T Kowalik; Jennifer A Steeden; John E Deanfield; Jens C Pruessner; Andrew M Taylor; Vivek Muthurangu (PLoS ONE)
Obesity and mental stress are potent risk factors for cardiovascular disease but their relationship with each other is unclear. Resilience to stress may differ according to adiposity. Early studies that addressed this are difficult to interpret due to conflicting findings and limited methods. Recent advances in assessment of cardiovascular stress responses and of fat distribution allow accurate assessment of associations between adiposity and stress responsiveness. We measured responses to the Montreal Imaging Stress Task in healthy men (N = 43) and women (N = 45) with a wide range of BMIs. Heart rate (HR) and blood pressure (BP) measures were used with novel magnetic resonance measures of stroke volume (SV), cardiac output (CO), total peripheral resistance (TPR) and arterial compliance to assess cardiovascular responses. Salivary cortisol and the number and speed of answers to mathematics problems in the task were used to assess neuroendocrine and cognitive responses, respectively. Visceral and subcutaneous fat was measured using T(2) (*)-IDEAL. Greater BMI was associated with generalised blunting of cardiovascular (HR:β = -0.50 bpm x unit(-1), P = 0.009; SV:β = -0.33 mL x unit(-1), P = 0.01; CO:β = -61 mL x min(-1) x unit(-1), P = 0.002; systolic BP:β = -0.41 mmHg x unit(-1), P = 0.01; TPR:β = 0.11 WU x unit(-1), P = 0.02), cognitive (correct answers: r = -0.28, P = 0.01; time to answer: r = 0.26, P = 0.02) and endocrine responses (cortisol: r = -0.25, P = 0.04) to stress. These associations were largely determined by visceral adiposity except for those related to cognitive performance, which were determined by both visceral and subcutaneous adiposity. Our findings suggest that adiposity is associated with centrally reduced stress responsiveness. Although this may mitigate some long-term health risks of stress responsiveness, reduced performance under stress may be a more immediate negative consequence.